2015
DOI: 10.1515/acph-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Facile heterocyclic synthesis and antimicrobial activity of polysubstituted and condensed pyrazolopyranopyrimidine and pyrazolopyranotriazine derivatives

Abstract: Reaction of 6-amino-3-methyl-4-(substituted phenyl)-1,4-dihydropyrano[2,3-c]pyrazole-5-carbonitrile (1) with triethylorthoformate followed by treatment with hydrazine hydrate, formic acid, acetic acid, phenylisocyanate, ammonium thiocyanate and formamide afforded the corresponding pyranopyrimidine derivatives 2-6. Cyclocondensation of 1 with cyclohexanone afforded pyrazolopyranoquinoline 7. One-pot process of diazotation and de-diazochlorination of 1 afforded pyrazolopyranotriazine derivative 8, which upon tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Polysubstituted and condensed pyrazolopyranopyrimidine and pyrazolopyranotriazine were developed by Hafez et al and were subsequently found to exhibit activity against certain microbial strains [56]. Compound (31) was the most active antifungal agent.…”
Section: Research In 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Polysubstituted and condensed pyrazolopyranopyrimidine and pyrazolopyranotriazine were developed by Hafez et al and were subsequently found to exhibit activity against certain microbial strains [56]. Compound (31) was the most active antifungal agent.…”
Section: Research In 2015mentioning
confidence: 99%
“…3]. Meanwhile, compound (32) exhibited excellent activity against bacteria which was higher or equal to MIC of norfloxacin [56]. Synthesis and antimicrobial screening of acetyl sulfonamide pyrazoles, substituted 4,5-dihydropyrazole-1carbothioamide and 4,5-dihydropyrazole-1-isonicotinoyl derivatives were presented by Hamada and Abdo [57].…”
Section: Research In 2015mentioning
confidence: 99%
“…The type of heteroatom and the ring size along with the substituent groups on the lead structure are the principal determinants of heterocycle’s physicochemical properties (Martins et al, 2015). Although there is a massive number of pharmacologically active heterocyclic compounds acting as antitumor (Chen et al, 2014, Sadhasivam et al, 2015, Abdel-Aziem, 2017), anti-fungal (Cao et al, 2014, Chitra et al, 2017, Zhao et al, 2017), anti-viral (Zhang et al, 2014, Da Costa et al, 2017, Asif, 2017), anti-inflammatory (Khan et al, 2012, Malik, 2016, Gomha et al, 2017) and anticonvulsant (Zayed, 2014, Shakya et al, 2016, Saravanan et al, 2017), an increasing number of heterocycles have shown a potent antibacterial effect (Azab et al, 2013, Hafez et al, 2015, Chand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by considering all of the above biological importance of pyrazole derivatives, and in continuation of our ongoing work [31][32][33][34]. We can say that pyrazole ring has been used for prospective development of new drug against cancer cell, so we designed and synthesized a series of novel pyrazole derivatives bearing imidiazole, pyrazole, oxazole, thiadiazole, benzochromene ring under microwave irradiation in the hope of obtaining novel antiproliferative agents.…”
Section: Introductionmentioning
confidence: 99%